Designing and Evaluating an Effective Online Training Program for Health Information Systems Implementation in Indonesia - Raharjo, Untoro Dwi (TIN: Terapan Informatika Nusantara, 2024)
Online training for health information system (HIS) introduction and capacity building offers a valuable solution for reaching remote healthcare providers. This approach provides cost-effectiveness and broad geographical reach. However, despite these advantages, online training presents several challenges, complicating its development. We aimed to design a precise online training program systematically which can be an alternative to reach remote healthcare providers. We also intend to give an important evaluation and possibility of online training in improving healthcare providers related to health information system. This paper shared insights from implementing online training for a zoonosis information system through an action research approach using a four-cycle process. We collaborated with stakeholders from various sectors, targeting healthcare providers at Primary Healthcare Centers (PHCs), zoonosis program coordinators from District and Provincial Health Offices across 10 regions in Indonesia, and national-level stakeholders. To ensure seamless online training, we used multiple platforms, including a Learning Management System, Wiki.js, Zoom Meetings, and an online discussion group. A hierarchical training model was developed, allowing national stakeholders to become trainers in future sessions. Despite the benefits in delivering new knowledge and experience in HIS, significant challenges included internet connectivity issues, affecting 60.00% of participants. The participants’ experience was a positive based on Community of Inquiry (CoI) evaluation framework. The evaluation showed that participants generally had a positive experience. Overall, online training proves to be an effective strategy for enhancing the information and technology skills of remote healthcare providers in HIS.